Effect of Balanced Fertilization and Mulching on Growth, Yield and Economics of Chilli (Capsicum annuum L.) in Odisha, India - , Mukhi S.K.; , Mishra P; , Bar N (Archives of Current Research International, 2025)
A front-line demonstration was carried out at different farmers’ field of Kandhamal district of Odisha to determine the effect of balanced fertilization and mulching on growth, yield and economics of chilli during 2022-23. The experiment was conducted under the international collaborative project on Resilience, Krishi Vigyan Kendra, Kandhamal, OUAT, Bhubaneswar. The demonstration was conducted at ten farmers’ field with three treatments viz., T1 : Farmer’s Practice (FYM @ 2 t ha-1 & N:P2O5:K2O::50:30:30 kg ha-1), without mulching, T2 : FYM @ 10 t ha-1 & N:P2O5:K2O @100:75:75 kg ha-1 , foliar application of water soluble fertilizer (19-19-19) and mulching with paddy straw @ 6 t ha-1 and T3: FYM @ 10 t ha-1 & N:P2O5:K2O @ 100:75:75 kg ha-1 , foliar application of water soluble fertilizer (19-19-19) and double coated (black on silver) polythene mulching. The results revealed that significantly higher growth parameters viz., plant height (89.6 cm), number of primary branches per plant (10.4) and plant spread (69.4 cm); yield attributes viz., number of fruits per plant (142.3), fruit length (6.41cm), fresh fruit weight (1.80 g), fruit dry weight (0.69 g ), fruit girth (2.73 cm) and fresh fruit yield (178.3 q ha-1) were observed with the treatment T3 (FYM 10 t ha-1,100% RDF, foliar application of water soluble fertilizer and polythene mulching) followed by T2 (FYM 10 t ha-1, 100% RDF, foliar application of water soluble fertilizer with paddy straw mulching @ 6 t ha-1). The highest number of weeds including grasses and broad leaf weeds (342.6 number of weeds m-2) was recorded in T1 (Farmer’s practice without mulching) plot followed by T2 (67.5 number of weeds m-2) and the lowest was in T3 (10.8 number of weeds m-2) indicating black polythene mulching was more effective than paddy straw mulching in suppressing weed growth. The treatments, received FYM 10 t ha-1,100% RDF, foliar spray with water soluble fertilizer and polythene mulching (T3) resulted in higher gross return of Rs. 4,45,750 ha-1, net return of Rs. 3,47,050 ha-1 and benefit: cost ratio of 4.5 as compared to T2 and T1. Hence, application of FYM @ 10 t ha-1, N:P2O5:K2O @ 100:75:75 kg ha-1, foliar application of water-soluble fertilizer and double coated (black on silver) polythene mulching enhanced the growth parameters, yield attributes, economic parameters and yield of chilli.